NEWS IN BRIEF. (Times Higher Education Supplement, 2005)
The article offers news briefs related to higher education in Great Britain as of December 9, 2005. The academics' pension contributions will remain unchanged despite a surplus in the Universities Superannuation Scheme. Technical support employees at Manchester University in England are planning to stage a strike over pay disparity. Research groups Pulse team and the European Social Survey has received €200,000 shares of the Descartes Research Prize.